ANALISIS KOMPARATIF FONEM BAHASA MELAYU RIAU DIELAEK ROKAN HILIR SUBDIALEK BAGAN SIAPI-API DENGAN SUBDIALEK PUJUD - Nurul Hardianti Hasibuan; Hasnah Faizah AR; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This study uses a common phoneme people often used Bagan Siapi-api and public Pujud and research found significant variations in language in trems of greeting someone from one place to another with the pronounciation, intonation or words uttered by the speaker differences within the region. This research was conducted in Rokan Hilr precisely in Bagan Siapi-api and in the district Pujud. The method used in this research is descriptive and comparative method that aims to describe and compare the type of phonemes found in Riau Malay Language Dialect Rokan Hilir Subdialek Bagan Siapi-api and Subdialek Pujud and this study used a qualitative approach. The result of this study to obtain three types of phonemes with details as follows: (1) six vocal phonemes, (2) twenty consonant phonemes (3) nine phonemes diphthongs and as many as 256 data.Keyword: comparative, phonemes, riau malay language, rokan hilir